The Meaning and Tradition of Sweeping in Mamala Village, Leihitu District, Central Maluku Regency - Kamsurya, Sarmita Ode; Iswatiningsih, Daroe (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Sweeping Stick Tradition is a cultural heritage of the Mamala community that takes place every 8 Syawal, passed down through generations. This tradition involves mutual beating with broomsticks until blood is drawn as a form of attraction and symbolizes the belief in the efficacy of Mamala oil. This research employs a descriptive qualitative method with purposive sampling techniques, involving 4 key informants from traditional leaders and village government. Data was collected through observation, interviews, and document studies. The results show that this tradition holds strong religious and brotherly meaning in the life of the Mamala community, and is preserved as a form of respect for ancestors and local beliefs.